INTERACTION OF SCHOOLCHILDREN WITH NATURE AS A SOCIO-PEDAGOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2022)
In clause the guestion on interaction of the school boys with a nature rises as racially pedagogical problem.
Keywords: 1